(untitled) (Anwer Khan Modern Medical College Journal, 2015)
Background: Adequate nutritional status of expectant mothers is essential for their health maintenance and good pregnancy outcome. To assess the anthropometric measurements of pregnant women. Methodology: Cross sectional study, 245 pregnant women was included whom attended at antenatal clinic of Dhaka Medical College hospital. Main outcome measures: 38% pregnant women were found with overweight or obese and 20% were found underweight that was related with chronic energy deficiency, vitamin deficiency and Iron deficiency anemia. Result: A total of 245 women were in this study, the highest number (48.16%) was found visited in the second trimester, 32.24% were in third and 19.5% in 1st trimester respectively. The mean age of women attending in this study was 23%. It was surprising that our upcoming mother’s did not have good height, around 60% were found less than five feet and 24% women were less than four feet eight inches, which indicated that a significant proportion of women might need to have surgical intervention during delivery. Not only the height, but also the weight of our respondents was found much poor and 16% of total attending women had weight below 40 kilogram. Conclusion: Our study revealed that the majority of the women suffered from chronic energy deficiency which could be the potential factor for delivering malnourished babies. All pregnant women should be motivated to have an antenatal check up throughout the pregnancy, increase birth spacing to hold their proper nutritional status and encourage them to delivery their babies in hospital. Anwer Khan Modern Medical College Journal Vol. 6, No. 1: January 2015, Pages 20-24